2016
DOI: 10.1590/0104-070720160002260015
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions About the Transition to Retirement: A Qualitative Study

Abstract: Retirement is a transitional life event that originates changes individuals have to adapt to and which leads to bio physiological, psychological and sociological vulnerabilities. The aim of this study was to understand how Portuguese retirees perceive their retirement experience. We conducted a qualitative study with 18 focus groups (146 participants recently retired), in health functional units located throughout the center region of mainland Portugal. Information was submitted to content analysis, using NViv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…Segundo essa autora, o rompimento do trabalho no horizonte profissional acarreta um estado de impotência no sujeito, que pode se sentir desamparado e angustiado. Desse modo, a literatura científica tem destacado a importância de se compreender as relações entre a aposentadoria e os processos de saúde e doença (Figueira, Haddad, Gvozd, & Pissinati, 2017;Loureiro, Mendes, Camarneiro, Silva, & Pedreiro, 2016;Torres, Camargo, Boulsfield, & Silva, 2015).…”
Section: Introductionunclassified
“…Segundo essa autora, o rompimento do trabalho no horizonte profissional acarreta um estado de impotência no sujeito, que pode se sentir desamparado e angustiado. Desse modo, a literatura científica tem destacado a importância de se compreender as relações entre a aposentadoria e os processos de saúde e doença (Figueira, Haddad, Gvozd, & Pissinati, 2017;Loureiro, Mendes, Camarneiro, Silva, & Pedreiro, 2016;Torres, Camargo, Boulsfield, & Silva, 2015).…”
Section: Introductionunclassified
“…A study that described the perception of the transition from worker to retiree identified that older adults exhibit, at this stage, issues related to the readjustment of life, whether personal or family, social and economic losses, and psycho-emotional and QoL gains. This transition process may be influenced by factors prior to retirement 14 .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the quality of collective life, Portugal has higher indices of poverty, inequality and lack of social assistance to retirees than other European Union countries (Rodrigues, 2003), especially with the fall in family income associated with retirement (Albuquerque, Arcanjo, Escária, Nunes, & Pereira, 2010;Valadas, Vilhena, & Fragoso, 2019). Despite this, according to Loureiro, Mendes, Camarneiro, Silva, and Pedreiro (2016), retirement is viewed throughout Europe as a period for living a calmer life and enjoying a pension accumulated over a lifetime of work. Fonseca (2006) points out that Portuguese retirees are reasonably satisfied, especially in the early years of their retirement.…”
Section: Introductionmentioning
confidence: 99%
“…• Hypothesis 1: Retirees living in Portugal will report greater levels of satisfaction with individual resources in retirement than will retirees living in Brazil, in light of the former country's higher quality of life (Pnud, 2019; Oliveira, Monteiro-Neto, Félix, Lima, & Almeida, 2017); • Hypothesis 2: Retirees living in Brazil will report higher levels of satisfaction with relationships in retirement than will retired people in Portugal. Although social support has been considered an important variable for retired people's well-being in both countries (Loureiro et al, 2016;Rafalski & Andrade, 2017), trans-cultural studies comparing Brazil with other countries have highlighted the extreme importance Brazilian retirees attribute to social relationships (França, 2008;França & Hershey, 2018) and the average level of satisfaction with marriage and family reported by Portuguese retirees (Fouquerau, Fernandez, Fonseca, Paul, & Uotinen, 2005). • Hypothesis 3: Retirees living in Portugal will present higher levels of satisfaction with the quality of collective resources in retirement than will retired people in Brazil.…”
Section: Introductionmentioning
confidence: 99%